Fitness consequences of anthropogenic subsidies for a partially migratory wading bird - Picardi, Simona; Frederick, Peter; Basille, Mathieu (Proceedings of the Royal Society. B, Biological sciences, 2024)
Human activities are forcing wildlife to confront selective pressures different from those under which they evolved. In seasonal environments, migration evolved as an adaptation to fluctuating resource availability. Anthropogenic subsidies modify resource dynamics by providing a steady food source that is not subject to seasonality. Globally, many migratory populations are becoming increasingly resident in response to food supplementation. While these population-level shifts are assumed to arise from changing fitness consequences of individual behaviour in response to resource dynamics, these mechanisms are often difficult to quantify and disentangle. Here, we quantified fitness consequences of responses to anthropogenic subsidies in partially migratory wood storks ( Mycteria americana ) in the heavily urbanized southeastern United States. First, we tested whether individual migratory behaviour is linked to different responses to anthropogenic subsidies. Second, we quantified fitness consequences of these behavioural responses. We found that, in our system, migration and residency are alternative behavioural tactics associated with different responses to food supplementation. In turn, the use of anthropogenic resources alters a fitness component by enhancing nest survival. These results provide a mechanistic examination of how animals may respond to human-modified resource dynamics and how fitness consequences of individual tactics may translate into behavioural shifts at the population level.